In search of the master therapist : emotional competence and client outcome : a thesis submitted in partial fulfilment of the requirements for the degree of Master in Psychology, Massey University, Palmerston North, New Zealand - de Vries, Ivor (Massey University, 2012)
Psychotherapy for clients is an interpersonal, often emotional, process facilitated under guidance from their therapist. Whilst the literature offers some tantalising clues as to which therapist-emotional qualities are beneficial for establishing good working relationships, which tend to lead to positive client change, little is known about which specific emotional skills successful therapists use to achieve this process. The purpose of the present study was to gain insight into how excellent therapists use their emotion in therapy to help clients achieve positive outcomes. Three therapists with high client outcome ratings engaged in semi-structured interviews, and resulting transcripts were analysed using interpretative phenomenological analysis. Participants spoke of genuine congruence in warmth and caring characteristics; sensitivity to client needs; harbouring positive expectations of their therapeutic methods and clients; possessing strong self-reflective and emotion regulation skills; often experiencing strong empathy but moderating their empathic expression; balancing the client relationship and therapeutic process; working collaboratively with their clients; and prioritising client emotional needs over their own. Implications, study limitations and future directions for research are discussed.
Keywords: Psychotherapist-client relationship; Emotion in psychotherapy; Psychotherapists; Psychotherapy